Internal-training-load monitoring, notational and time-motion analyses, psychometric status, and neuromuscular responses in elite rugby union - Lupo, C.; Ungureanu, A. N.; Boccia, G.; Licciardi, A.; Rainoldi, A.; Brustio, P. R. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The present study aimed to verify if practicing tackles during rugby union training sessions would affect the players` internal training load and acute strength loss. Method: A total of 9 male Italian Serie A rugby union players (age: 21 [2] y) were monitored by means of an integrated approach across 17 sessions, 6 with tackles (WT) and 11 with no tackles (NT). Edwards training load was quantified using heart-rate monitoring. Global positioning system devices were used to quantify the total distance and time at >20 W. Work-to-rest ratio was quantified by means of a video analysis. Before (PRE) and after (POST) the session, the players` well-being and rating of perceived exertion were measured, respectively. The countermovement jump and plyometric push-up jump tests were performed on a force plate to record the players` PRE-POST concentric peak force. Linear mixed models were applied to quantify the differences between WT and NT in terms of training load and PRE-POST force deltas, even controlling for other training factors. Results: The Edwards training load (estimated mean [EM]; standard error [SE]; WT: EM = 214, SE = 11.8; NT: EM = 194, SE = 11.1; P = .01) and session rating of perceived exertion (WT: EM = 379, SE = 21.9; NT: EM = 277, SE = 16.4; P < .001) were higher in WT than in NT. Conversely, no difference between the sessions emerged in the countermovement jump and plyometric push-up concentric peak force deltas. Conclusions: Although elite rugby union players` external and internal training load can be influenced by practicing tackles, upper- and lower-limb strength seem to not be affected.